Prolonged cycling exercise alters neural control strategy, irrespective of carbohydrate dose ingested - Newell, M. L.; Macgregor, L. J.; Galloway, S. D. R.; Hunter, A. M. (Translational Sports Medicine, 2021)
The interactions between CHO dosage and neuromuscular regulation following fatiguing endurance exercise are not well understood. Fifteen well-trained male cyclists completed 4 experimental trials of 120-min submaximal cycling (95% lactate threshold) during which water (0 g CHO·h-1) or CHO beverages (20, 39, or 64 g CHO·h-1) were consumed every 15 minutes, at a rate of 1 L·h-1, followed by a work-matched time trial ~30 minutes. Maximal voluntary contraction (MVC), M-wave twitch potentiation and torque, motor unit recruitment and firing rate were recorded pre- and post-cycling. Time trial performance improved following 39 and 64 versus 0 and 20 g CHO·h-1, with no effect of CHO dose on any pre- to post-neuromuscular function measures. Pre- to post-cycling exercise: (1) MVC, and M-wave amplitude and duration declined by -21.5 Nm, and -4.9 mV and -7.1 ms, respectively; (2) peak evoked torque remained unchanged; (3) Firing rate of early- and mid-recruited motor units increased by 0.93 pps and 0.74 pps, respectively, with no change in later-recruited motor units. Thus, central drive to early- and mid-recruited motor units increases as a result of endurance cycling, due to a likely fatigue compensatory mechanism. However, CHO availability does not appear to influence increased neuromuscular drive.